Cardiovascular Safety of Tocilizumab Versus Etanercept in Rheumatoid Arthritis: A Randomized Controlled Trial. Issue 1 (27th December 2019) - Giles, Jon T.; Sattar, Naveed; Gabriel, Sherine; Ridker, Paul M.; Gay, Steffen; Warne, Charles; Musselman, David; Brockwell, Laura; Shittu, Emma; Klearman, Micki; Fleming, Thomas R.
Abstract : Objective: To assess the risk of major adverse cardiovascular events (MACE) in patients with rheumatoid arthritis (RA) treated with tocilizumab compared to those treated with the tumor necrosis factor inhibitor etanercept. Methods: This randomized, open‐label, parallel‐group trial enrolled patients with active seropositive RA (n = 3, 080) who had an inadequate response to conventional synthetic disease‐modifying antirheumatic drugs and who had at least 1 cardiovascular (CV) risk factor. Patients were randomly assigned 1:1 to receive open‐label tocilizumab at 8 mg/kg/month or etanercept at 50 mg/week. All patients were followed up for a mean of 3.2 years. The primary end point was comparison of time to first occurrence of MACE. The trial was powered to exclude a relative hazard ratio for MACE of 1.8 or higher in the tocilizumab group compared to the etanercept group. Results: By week 4 of treatment, the serum low‐density lipoprotein cholesterol, high‐density lipoprotein cholesterol, and triglyceride levels were a median 11.1%, 5.7%, and 13.6% higher, respectively, in patients receiving tocilizumab compared to those receiving etanercept (each P < 0.001). During follow‐up, 83 MACE occurred in the tocilizumab group compared to 78 MACE in the etanercept group. The estimated hazard ratio for occurrence of MACE in the tocilizumab group relative to the etanercept group was 1.05 (95% confidence interval 0.77–1.43). Results were similar in sensitivity analyses and in the on‐treatment population analysis. Adverse events occurred more frequently in the tocilizumab group, including serious infection and gastrointestinal perforation. Conclusion: The results of this trial, which provide insights into the CV safety of tocilizumab as compared to etanercept, ruled out a risk for occurrence of MACE of 1.43 or higher in patients treated with tocilizumab. This result should be interpreted in the context of the clinical efficacy and non‐CV safety of tocilizumab.